Metabolomics reveals highly regional specificity of cerebral sexual dimorphism in mice. (January 2020) - Chabrun, Floris; Dieu, Xavier; Rousseau, Guillaume; Chupin, Stéphanie; Letournel, Franck; Procaccio, Vincent; Bonneau, Dominique; Lenaers, Guy; Simard, Gilles; Mirebeau-Prunier, Delphine; Chao de la Barca, Juan Manuel; Reynier, Pascal
Highlights: Half of the analyzed metabolites show a sexual dimorphism in the mice brain. Sexual dimorphism in the brain is highly regional-specific. Sexual dimorphism affects a wide range of functions and structures in the brain. Abstract: The development of personalized medicine according to gender calls for the integration of sexual dimorphism in pre-clinical models of diseases. Although sexual dimorphism in the brain of the mouse has been the subject of several behavioral, neuroimaging and experimental studies, very few have characterized the bases of sexual dimorphism in the brain on the omics scale. In particular, physiological variations in metabolomic and lipidomic terms related to gender have not been mapped in the brain. We carried out a metabolomic analysis, targeting 188 metabolites representative of various cellular structures and metabolisms, in three brain regions: frontal cortex, brain stem and cerebellum, in 3-month-old C57BL-6 J male (n = 20) vs. female (n = 20) mice. Our results demonstrate the existence of sexual dimorphism in the whole brain as well as in separate brain regions. Half of the 129 accurately measured metabolites were involved in the sexual dimorphism of the murine brain, but only 8% of those (hydroxyproline, creatinine, hexoses, tryptophan, threonine and lysoPC.a.C18.2) were involved in common in the three cerebral regions, while 71%, including phosphatidylcholines, lysophosphatidylcholines, sphingomyelins, acylcarnitines, amino acids, biogenic amines, and polyamines, were specific to only one region of the brain, underscoring the highly regional specificity of cerebral sexual dimorphism in mice.